2017
DOI: 10.1016/j.nmd.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset of ambulation in boys with Duchenne muscular dystrophy: Potential use as an endpoint in clinical trials

Abstract: Individuals with Duchenne muscular dystrophy (DMD) often exhibit delayed motor and cognitive development, including delayed onset of ambulation. Data on age when loss of independent ambulation occurs are well established for DMD; however, age at onset of walking has not been well described. We hypothesize that an effective medication given in early infancy would advance the age when walking is achieved so that it is closer to age-matched norms, and that this discrete event could serve as the primary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The life-limiting nature of DMD strongly affects both patients and parents, who are required to navigate numerous challenges, which may include: fatigue , which can be acute (e.g., following exertion) or chronic (El-Aloul & Campbell, 2017); pain , which is often linked to muscle cramps and joint pain (Jacques et al, 2019); discomfort and sleep disturbance from wearing night splints to manage limb contractures (Apkon et al, 2018); constipation , as a result of limited physical activity (Kraus et al, 2016); loss of ambulation , which occurs by 12 years (Gissy et al, 2017); and late symptoms, which may include difficulties with speech and swallowing (dysphagia) (Toussaint et al, 2016). Approximately 26% of individuals with DMD have an intellectual disability while prevalence rates of ADHD are around 32% (Colvin et al, 2018), and co-occurrence of Autism spectrum disorder (ASD) was found in 21% of cases by Ricotti et al (2016).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The life-limiting nature of DMD strongly affects both patients and parents, who are required to navigate numerous challenges, which may include: fatigue , which can be acute (e.g., following exertion) or chronic (El-Aloul & Campbell, 2017); pain , which is often linked to muscle cramps and joint pain (Jacques et al, 2019); discomfort and sleep disturbance from wearing night splints to manage limb contractures (Apkon et al, 2018); constipation , as a result of limited physical activity (Kraus et al, 2016); loss of ambulation , which occurs by 12 years (Gissy et al, 2017); and late symptoms, which may include difficulties with speech and swallowing (dysphagia) (Toussaint et al, 2016). Approximately 26% of individuals with DMD have an intellectual disability while prevalence rates of ADHD are around 32% (Colvin et al, 2018), and co-occurrence of Autism spectrum disorder (ASD) was found in 21% of cases by Ricotti et al (2016).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Sarah’s wellbeing was understandably impacted by the stage of transition that she and Sam encountered during the course of therapy; Sam had reached the period in adolescence when ambulation had deteriorated (Gissy et al, 2017), and he required more personal care form Sarah. As suggested in the literature, this transitional stage was challenging (Pangalila et al, 2012), as Sarah was required to find even more time in the day to learn how to use new assistive technology, which took repeated attempts and additional support form an occupational therapist to master.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…Patients with early childhood treatment had slightly decreased respiratory function compared with those who had late childhood treatment. Gissy, 2017 35 Born 1982-2011; DMD only; n ¼ 463 Data on initiation of ambulation from MD STARnet were compared with data from other cohort and registry-based studies. Boys with DMD, on average, started walking later than boys with a typical developmental trajectory (17 mo as compared to 12 mo).…”
Section: Diagnostic Process and Disease Progressionmentioning
confidence: 99%
“…A 'time to event' outcome measure may also be applicable to young DMD patients. It is known that DMD patients achieve the ability to walk generally later than healthy peers [20] . As such, achieving the ability to walk might be a potential candidate for an outcome measure to be used when treating very young DMD patients.…”
Section: Lessons Learnt and Preparing For The Futurementioning
confidence: 99%